Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-69008
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Analysis of Indirect Combustion Noise in Subcritical Nozzles

Abstract: This article revisits the problem of indirect combustion noise in nozzles of finite length. The analytical model proposed by Moase et al. (JFM 2007) for indirect combustion noise is red-erived and applied to subcritical nozzles having shapes of increasing complexity. This model is based on the equations formulated by Marble & Candel (JSV 1977) for which an explicit solution is obtained in the subsonic framework. The discretization of the nozzle into n elementary units of finite length implies the determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…In this article, they also propose a methodology to extend its capabilities to arbitrarily shaped nozzles. The present authors have recently worked on this idea and shown that the model can indeed be extended and applied to arbitrarily shaped nozzles and provide their acoustic transfer functions both for direct and indirect combustion noise [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this article, they also propose a methodology to extend its capabilities to arbitrarily shaped nozzles. The present authors have recently worked on this idea and shown that the model can indeed be extended and applied to arbitrarily shaped nozzles and provide their acoustic transfer functions both for direct and indirect combustion noise [12].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to ensure the nozzle compactness for all simulated configurations, the compactness criterion Ω 0 = ω 0 × L 0 dξ/u(ξ ), where ω 0 = 2πf 0 is the angular frequency of the forcing signal and L the axial length of the nozzle, has been calculated and is reported in table 5. This criterion was initially proposed by Giauque et al (2012) and represents the ratio between the time needed by the entropy wave to pass through the nozzle and its period τ 0 = 1/f 0 . Its low value indicates that the fluctuation can indeed be considered constant through the entire nozzle, so that the nozzle appears to be compact even for frequencies several times larger than f 0 .…”
Section: Huet and A Giauquementioning
confidence: 99%
“…These conditions allow acoustic and entropy waves to leave the domain without noticeable reflections and are modified to inject pressure and temperature fluctuations (Kaufmann, Nicoud & Poinsot 2002). The reader may refer to Giauque et al (2012) for additional details on the solver and its validation.…”
Section: Numerical Validationmentioning
confidence: 99%
See 2 more Smart Citations